ANALYSIS THE EFFECT OF THE INFLATION, GROSS DOMESTIC PRODUCT, THIRD PARTY FUNDS, AND MARKET SHARE FACTORS TO THE PROFITABILITY OF THE ISLAMIC BANKING INDUSTRY IN INDONESIA ON PERIOD 2018-2023 - Arham, Muhammad Dai; Atika; Inayah, Nurul (I-Economics, 2024)
This research aims to determine the influence of Inflation, Gross Domestic Product, Third Party Funds and Market Share on the Profitability of the Sharia Banking Industry for the 2018-2023 period. This research uses descriptive quantitative methods. The data used in this research uses secondary data obtained from quarterly Central Statistics Agency and Financial Services Authority reports. The number of samples in this research was 80 data. The data analysis technique used is Multiple Linear Regression. The research results show that inflation has a partial effect on profitability. Gross Domestic Product has the opposite effect on profitability. Third Party Funds and Market Share have a positive and significant effect. Simultaneously, Third Party Funds and market share have a significant effect on profitability.